Synthesis, solid-state fluorescence properties, and computational analysis of novel 2-aminobenzo[4,5]thieno[3,2-d]pyrimidine 5,5-dioxides - Yokota, Kenichirou; Hagimori, Masayori; Mizuyama, Naoko; Nishimura, Yasuhisa; Fujito, Hiroshi; Shigemitsu, Yasuhiro; Tominaga, Yoshinori (Beilstein Journal of Organic Chemistry, 2012)
New fluorescent compounds, benzo[4,5]thieno[3,2-d]pyrimidine 5,5-dioxides (3a–g), 2-amino-4-methylsulfanylbenzo[4,5]thieno[3,2-d]pyrimidine (6), and 2-amino-4-methylsulfanyl-7-methoxybenzo[4,5]furo[3,2-d]pyrimidine (7), were synthesized in good yields from heterocyclic ketene dithioacetals (1a–c) and guanidine carbonate (2a) or (S)-methylisothiourea sulfate (2b) in pyridine under reflux. Among the fused pyrimidine derivatives, compound 3c, which has an amino group at the 2-position and a benzylamino group at the 4-position of the pyrimidine ring, showed the strongest solid-state fluorescence. The absorption and emission properties of the compounds were quantitatively reproduced by a series of ab initio quantum-chemical calculations.
Keywords: amino group; fluorescence; HOMO/LUMO; pyrimidine; solid-state